A comparative evaluation of myeloid-derived suppressor cells and murine double minute 2 in Iraqi breast cancer patients before therapy (Journal of the College of Basic Education, 2026)
Background: Breast cancer (BC) is the most prevalent and life-threatening form of cancer, with a high rate of mortality. Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells that overexplicitly proliferate in cancer and have potent immunosuppressive capacity. In the meantime, murine double minute 2 (MDM2) is also known to play an oncogenic role, especially in the development of breast cancer.Objective: This paper was designed to evaluate MDSCs and MDM2 as possible indicators to distinguish between patients with BC prior to treatment and healthy persons.Methods: In this case-control study, a total of 90 participants were enrolled, including 65 newly diagnosed, untreated breast cancer patients (cases) and 25 healthy individuals (controls). All patients were recruited from the Oncology Teaching Hospital in Baghdad, Iraq. The enzyme-linked immunosorbent assay (ELISA) is used to measure the total levels of both MDSCs and MDM2 in peripheral blood. Results: The results of the current study indicated that the serum level of MDSCs was highly significant in breast cancer patients before receiving therapy (P≤0.001) compared with healthy controls. Furthermore, the MDM2 was also more elevated in BC patients than in healthy controls (P≤0.05).Conclusion: In conclusion, the study found a highly significant difference in serum MDSCSs in BC patients before treatment compared to the control. We also observed elevated levels of MDM2 in BC patients, which we attributed to the onset of cancer.